2022
DOI: 10.1002/psc.3463
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, cytotoxic, and insulin‐releasing activities of the amphibian host‐defense peptide ocellatin‐3N and its L‐lysine‐substituted analogs

Abstract: The host-defense peptide ocellatin-3N (GIFDVLKNLAKGVITSLAS.NH 2 ), first isolated from the Caribbean frog Leptodactylus nesiotus, inhibited growth of clinically relevant Gram-positive and Gram-negative bacteria as well as a strain of the major emerging yeast pathogen Candida parapsilosis. Increasing cationicity while maintaining amphipathicity by the substitution Asp 4 !Lys increased potency against the microorganisms by between 4-and 16-fold (MIC ≤3 μM) compared with the naturally occurring peptide. The subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…When studying the ocellatins (LB1, LB2, and F1) from L. labyrinthicus, Gusmão et al [22] showed activity against E. coli, and specifically, ocellatin-F1 was active on S. aureus. Colon et al [28] isolated ocellatin-3N from Leptodactylus nesiotus and reported its ability to inhibit the growth of A. baumannii and P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…When studying the ocellatins (LB1, LB2, and F1) from L. labyrinthicus, Gusmão et al [22] showed activity against E. coli, and specifically, ocellatin-F1 was active on S. aureus. Colon et al [28] isolated ocellatin-3N from Leptodactylus nesiotus and reported its ability to inhibit the growth of A. baumannii and P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, antimicrobial peptides cause minimal damage to host cells and enhance host immune function, aiding in disease recovery and maintaining physiological functions [28,29]. Furthermore, antimicrobial peptides have potential effects such as anti-inflammatory properties [30,31], anticancer properties [32], and insulin-release promotion [33][34][35], indicating their potential as antibiotic alternatives. However, compared to antibiotics, the pharmacological properties of antimicrobial peptides are still under investigation, and their clinical applications are in the early stages, necessitating further research and development for widespread use.…”
Section: Introductionmentioning
confidence: 99%